Consumer Protection In Islamic Law: Thematic Analysis Of Hadith On Khiyar in Islamic Law and Its Contextualization In The Digital Age - Muh Tabran; Muhammadiyah Amin; Abdul Rahman Sakka (PT. Padang Tekno Corp, 2026)
This study aims to examine the authenticity of Sahih Bukhari Hadith No. 2112 regarding the right of khiyar through a comprehensive takhrij method to ensure the validity of the evidence in muamalah policy. Additionally, this study examines the mechanism of transmitting legal texts without editorial changes and compares the ijtihad of the four schools of jurisprudence regarding time limits to provide consumer protection solutions in the digital age. The methodology employed is normative legal research using a descriptive-analytical qualitative approach through library research. Data collection techniques involved cataloging hadiths on khiyar from the Kutubus Sittah, identifying the structure of the isnad, and analyzing key vocabulary (mufradat). Data analysis was conducted through stages of isnad criticism to assess the quality of the narrators, systematic analysis of the matn, comparative analysis across schools of thought, and the synchronization of traditional principles with modern economic realities. The research results indicate that the hadiths on khiyar possess exceptional chain of transmission quality within the Silsilah adz-Dzahab tradition, ensuring the text’s accuracy free from distortion over fourteen centuries. Regarding the time limit for khiyar syarat, differing viewpoints were identified: the Shafi’i school limits it to a maximum of three days, while the Maliki school allows a duration of up to 38 days depending on the type of object. In conclusion, the principle of khiyar remains relevant in the digital economy through the transformation of the order cancellation feature as a manifestation of khiyar majelis, as well as the return policy as an application of khiyar aib and khiyar syarat. The implications of this research emphasize that the ethical values of khiyar can serve as a foundation for regulators in refining consumer protection laws to minimize information asymmetry and ensure full consent (antaradin) in every online transaction